“Living by Others”: Work Performance and Basic Need Fulfillment Among Women Farmworkers - Anggaunitakiranantika Anggaunitakiranantika (JSP (Jurnal Ilmu Sosial dan ilmu Poltik), 2022)
This article explores Indonesian women who work as farmworkers, whose lives depend on working on other people’s agricultural land. The income earned by the women farmworkers is not high since female farm work is a seasonal job in agriculture. This research was conducted in Banyuwangi Regency as one of the largest farming areas in East Java Province, Indonesia, using a qualitative method with a phenomenological approach. Purposive sampling is a chosen technique in this research, involving ten women farmworkers, a farmworker spouse, and two landlords. Combining Scott’s subsistence ethics and existentialist feminism by Beauvoir, the research found that the work performed by women in East Java, Indonesia is a form of women’s existentialism that is carried out by experiential knowledge in working capabilities, constructing equality and gender roles through the men-women division of labor, and strengthening women farmworkers identification through work. Furthermore, women farmworkers make various efforts to fulfill their basic needs as their subsistence ethics. They utilize various side jobs that they can still do, reducing expenses and being owed by relatives, neighbors, and rice field owners in their hometown.